The Impact of the German Strategy for Containment of Coronavirus SARS-CoV-2 on Training Characteristics, Physical Activity and Sleep of Highly Trained Kayakers and Canoeists: A Retrospective Observational Study - Zinner, Christoph; Matzka, Manuel; Leppich, Robert; Kounev, Samuel; Holmberg, Hans-Christer; Sperlich, Billy (Frontiers in Sports and Active Living, 2020)
Aim: To characterize the impact of the German strategy for containment of Coronavirus SARS-CoV-2 (social distancing and lockdown) on the training, other habitual physical activity, and sleep in highly trained kayakers and canoeists. Method: During the 4 weeks immediately prior to and following the beginning of the German government's strategy for containment of Coronavirus SARS-CoV-2 on March 23, 2020, 14 highly trained athletes (VO2peak: 3,162 ± 774 ml/min; 500-m best time: 117.9 ± 7.9 s) wore a multi-sensor smartwatch to allow continuous assessment of heart rate, physical activity, and sleep duration. Result: In comparison to before lockdown, the overall weekly training time and the average length of each session of training during the lockdown decreased by 27.6% (P = 0.02; d = 0.91) and 15.4% (P = 0.36; d = 0.36), respectively. At the same time, the number of sessions involving specific (i.e., canoeing and kayaking) and non-specific (i.e., running, cycling) training, respectively, did not change (P = 0.36–0.37; d = 0.34–0.35). The number of sessions involving strength (+17.4%; P = 0.03; d = 0.89) or other types of training (+16.7%; P = 0.06; d = 0.75) increased during the lockdown with 2.8–17.5% more training time involving a heart rate <60%, 82–88, 89–93, or 94–100% of individual peak heart rate (HRpeak) (P = 0.03–0.86; d = 0.07–1.38), and 4.3–18.7% less time with a heart rate of 60–72 or 73–83% HRpeak (P = < 0.001–0.0.26; d = 0.44–2.24). The daily duration of sleep was 30 min (6.7%) longer during the lockdown (P < 0.001; d = 1.53) and the overall time spent lying down was 17% greater (P < 0.001; d = 2.26); whereas sitting time (−9.4%; P = 0.003; d = 1.23), the duration of light (15 min; −7.3%; P = 0.04; d = 0.83), and moderate (−18.6%; P = 0.01; d = 1.00) physical activity other than training (−9.4%; P = 0.22; d = 0.00) were all lower during lockdown. Conclusion: The present data revealed that following the German lockdown for containment of the Coronavirus SARS-CoV-2, highly trained kayakers and canoeists spent less overall time training each week (−27.6%) with, on average, shorter training sessions (−15.1%) and less light-to-moderate physical activity outside of training. Moreover, they performed more strength training sessions per week, and all engaged in more training at intensities >82 and <60% of HRpeak and spent longer periods lying down and sleeping during the lockdown.